A 2‐element meandered‐line slot‐based frequency reconfigurable MIMO antenna system. Issue 11 (16th October 2018) - Raza, A.; Khan, Muhammad U.; Tahir, Farooq A.; Hussain, R.; Sharawi, Mohammad S.
Abstract: A dual‐band frequency reconfigurable multiple‐input multiple‐output (MIMO) antenna system is presented. The design consists of two slot‐based antenna elements made on an FR4 board and occupies an area of 50 × 100 mm 2 . The antenna operates in two bands. Further, a varactor diode is integrated across the slot to achieve the frequency reconfiguration. The antenna can be reconfigured to operate in both bands from 1.35‐1.62 GHz and 1.95‐2.2 GHz with minimum −6 dB bandwidth of 50 MHz. A defected ground structure (DGS) between the antenna elements is used to improve the isolation. With compact size and low envelope correlation coefficient (ECC), the design is suitable for long‐term evolution (LTE) systems and cognitive radio (CR) enabled platforms.